2012
DOI: 10.2169/internalmedicine.51.6214
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Japanese Spotted Fever Complicated with Central Nervous System Involvement and Multiple Organ Failure

Abstract: Japanese spotted fever (JSF), first reported in 1984, is a rickettsial disease characterized by high fever, rash, and eschar formation. A 61-year-old man was admitted to a local hospital in Nagasaki City, Japan, after several days of high fever and generalized skin erythema. His condition deteriorated and laboratory findings indicated disseminated intravascular coagulation (DIC). The patient was transferred to our hospital with mental disturbance and status epilepticus. Treatment included minocycline, and new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…These authors have reported EEG slowing even in clinically normal patients with Rocky Mountain spotted fever 28 29. EEG changes in 4 patients with R. japonicum revealed slowing in 2, sharp waves in 1 and normal findings in 1 patient; 3 of these patients had seizures 30. EEG slowing is common in patients with arbovirus encephalitis such as in Japanese encephalitis and dengue 31 32…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These authors have reported EEG slowing even in clinically normal patients with Rocky Mountain spotted fever 28 29. EEG changes in 4 patients with R. japonicum revealed slowing in 2, sharp waves in 1 and normal findings in 1 patient; 3 of these patients had seizures 30. EEG slowing is common in patients with arbovirus encephalitis such as in Japanese encephalitis and dengue 31 32…”
Section: Discussionmentioning
confidence: 98%
“…All these patients received late treatment 37. In a study on 5 patients with CNS involvement due to Japanese spotted fever, CT revealed subdural haematoma in 1 of 4 patients and MRI performed on 1 patient was normal 30. Similarly, subtle MRI changes have also been reported in septic encephalopathy, which do not influence in the patient’s management 38.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the spotted fever group (SFG) R. japonica is considered to be the most important Rickettsia sp. in Japan because of its potential zoonoses, higher occurrence and potential severity, which can be fatal in humans [23,24,28].…”
mentioning
confidence: 99%
“…Meningoencephalitis, behavior and memory disturbances as delayed consequences have been published, although recovery occurs (Silpapojakul et al, 1991;Masalha et al, 1998;Moy and Ooi, 2015;Simon et al, 2011;Massung et al, 2001;Dittrich et al, 2015;Samra et al, 1989;Carr et al, 2014). Status epilepticus has been described in Japanese spotted fever, which is caused by Rickettsia japonica (Nakata et al, 2012) as well as in MT with fatality (Stephens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%